Of luck and inspiration - Sihoe, Alan D. L. (Video-Assisted Thoracic Surgery; Vol 1 (September 2016): Video-Assisted Thoracic Surgery, 2016)
Many of you see Diego Gonzalez Rivas as a maverick pioneer in Minimally Invasive Thoracic Surgery, a masterful educator in operative technique, or simply the rock-star of Thoracic Surgery. I happen to know him as one of my best friends inside and outside the world of surgery. And I am luckier than you because I have seen some sides of this man that you may never see. Let me share just four of these sides of ‘xiao gan’ (little Gonzalez) with you.